Coordinate control of multi-infeed VSC-HVDC for enhancing power system reliability - Kwanghyun Kim; Yoongun Jung; Minhyeok Chang; Junsang Cha; Seokjun Kang; Hyunkeun Ku; Gumin Kwon; Minhan Yoon; Gilsoo Jang (International Journal of Electrical Power & Energy Systems)
The growing disparity between power generation and consumption areas, along with the increasing integration of renewable energy, has led to system congestion and overvoltage issues. To address this issue, this paper proposes a coordinated control approach a multi-infeed voltage source converter (VSC) high-voltage direct current (HVDC) with linearization. The proposed method analyzes the impact of VSC-HVDC active and reactive power control on line loading and bus voltage variations to define the HVDC control area. To prevent counteracting effects during multi-terminal HVDC control, the line loading and bus voltage are formulated as linear equations, and the optimal HVDC operating points are determined through optimization. Based on this, a min-max linear programming problem is formulated and reformulated into a mixed-integer linear programming (MILP) problem using the Big-M method. The proposed approach is validated through simulations on the Korea power system, demonstrating its effectiveness in mitigation line loading and bus voltage fluctuations.